Effect of Traditional Chinese Medicine nursing under the theory of symptom management on the treatment of chemotherapy-induced nausea and vomiting in patients with gynecological tumor (症状管理理论下中医护理方案对妇科肿瘤患者化疗相关性恶心呕吐的干预效果) - WEI Xiaolin (魏小林); LIU Dan (刘丹); XU Xuewen (徐雪雯); LIU Hui (刘慧) (中西医结合护理)
Objective To explore the effect of Traditional Chinese Medicine nursing under the theory of symptom management on the treatment of chemotherapy-induced nausea and vomiting in patients with gynecological tumor. Methods From March 2023 to March 2024, 60 patients with gynecological tumor undergoing chemotherapy were selected as the research objects, and they were randomly divided in to the study group (n=30) and control group (n=30). The control group received routine nursing, while xperimental group received auricular point sticking, acupressure and aromatherapy on the basis of routine nursing. The MASCC scale and The WHO quality of life assessment instrument (WHOQOL-Bref) were used to evaluate the patients after the first course chemotherapy (T1), the second course chemotherapy (T2), the third course chemotherapy (T3) and the fourth course chemotherapy (T4). Results After the intervention, there was a significant difference in the score of delayed nausea between the two groups(F=5. 408, P<0. 05), but there was no significant difference in the score of acute nausea(F=2. 467, P＞0. 05). In addition, here were statistically significant differences in the physical field, psychological field and environmental field of WHOQOL-BREF between the two groups(P<0. 05). Conclusion Traditional Chinese Medicine nursing is beneficial to reduce the severity of delayed nausea and vomiting and improve the quality of life of patients with gynecological cancer chemotherapy. (目的 探讨症状管理理论下中医护理技术对妇科肿瘤患者化疗相关性恶心呕吐的干预效果。方法 2023年3月—2024年3月, 选取医院妇科肿瘤化疗患者60例为研究对象, 随机分为试验组和对照组, 各30例。对照组接受常规护理, 试验组在常规护理的基础上接受中医护理干预方案。采用MASCC止吐量表、生命质量测定简表(WHOQOL-BREF), 分别于第1次化疗后(T1)、第2次化疗后(T2)、第3次化疗后(T3)和第4次化疗后(T4)对患者进行评估。结果 干预后, 两组延迟性恶心得分存在组间差异(F=5. 408, P＜0. 05), 而急性恶心得分差异无统计学意义(F=2. 467, P＞0. 05)。两组WHOQOL-BREF简表的生理领域、心理领域、环境领域比较, 差异有统计学意义(P＜0. 05)。结论 症状管理下中医护理方案有利于减轻妇科肿瘤化疗患者延迟性恶心呕吐的发生及严重程度, 提高生活质量。)